Conditional cooperation and betrayal aversion - Cubitt, Robin; Gaechter, Simon; Quercia, Simone (Elsevier, 2017)
We investigate whether there is an association between conditional cooperation and betrayal aversion, two phenomena that we conjecture share common psychological characteristics despite having been studied largely separately in the previous literature. We use a public goods game to categorize subjects by type of contribution preference and we measure betrayal aversion for different categories of subject. We report three studies, using two different methods to measure betrayal aversion: a standard elicitation with monetary incentives and a novel scenario-based measure that we argue addresses concerns about the standard measure. We find strong and robust evidence of an association between conditional cooperation and betrayal aversion in the scenario-based measures but not in the standard measure.